Remote clinical decision making: Evaluation of a new education module. (March 2018) - Brady, Mike; Jackson, Joni; Northstone, Kate
Highlights: The need for HCPs to make decisions about patients remotely will increase. An educational module on Remote Clinical Decision Making (RCDM) was developed. Participant confidence in making decisions remotely increased after the module. Future delivery would benefit from tailoring to participants needs and experience. Future research should assess impact on working practice and patient/economic benefit.